Analytical model for flexible pipe armor wire lateral instability - Li, Xiaotian (2019)
The offshore oil and gas industry has been confronted with the issue of armor wire lateral instability in unbonded flexible pipes for over two decades. The objective of the present thesis is by theoretical as well as experimental means to investigate the underlying mechanism of the armor wire lateral instability. Analytical model is developed to describe the armor wire deflection in a flexible pipe subjected to a constant axial compressive load combined to cyclic bending. This model is capable of evaluating the equilibrium path of the armor wire after numerous bending cycles in stable states, as well as estimating the critical axial compressive load that may cause the armor wire lateral instability failure. Two flexible pipes are tested in a hyperbaric chamber applying high hydrostatic pressure combined to numerous bending cycles. The obtained test data, as well as that available in the literature, is compared with the armor wire lateral stability limit estimated by the present analytical model, showing excellent agreement. Also, some useful suggestions for improving the flexible pipe design against the armor wire lateral instability are presented.